2010
DOI: 10.1063/1.3326942
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature exfoliation process in hydrogen-implanted germanium layers

Abstract: The feasibility of transferring hydrogen-implanted germanium to silicon with a reduced thermal budget is demonstrated. Germanium samples were implanted with a splitting dose of 5×1016 H2+ cm−2 at 180 keV and a two-step anneal was performed. Surface roughness and x-ray diffraction pattern measurements, combined with cross-sectional TEM analysis of hydrogen-implanted germanium samples were carried out in order to understand the exfoliation mechanism as a function of the thermal budget. It is shown that the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 16 publications
3
42
0
Order By: Relevance
“…Both effects (voids and strain generation) are minimized as to ensure optimum bond strength. The samples described in Table I have been selected in order to carry out an in-depth analysis of a two-step low-temperature exfoliation process previously reported in (3). In the latter, experimental evidence of complete exfoliation of the germanium layer is demonstrated in an H-implanted Ge layer bonded to a host silicon wafer covered with a thick silicon dioxide layer, hence demonstrating the excellent bond strength between the exfoliated Ge and the host wafer.…”
Section: Methodsmentioning
confidence: 99%
“…Both effects (voids and strain generation) are minimized as to ensure optimum bond strength. The samples described in Table I have been selected in order to carry out an in-depth analysis of a two-step low-temperature exfoliation process previously reported in (3). In the latter, experimental evidence of complete exfoliation of the germanium layer is demonstrated in an H-implanted Ge layer bonded to a host silicon wafer covered with a thick silicon dioxide layer, hence demonstrating the excellent bond strength between the exfoliated Ge and the host wafer.…”
Section: Methodsmentioning
confidence: 99%
“…Mechanisms explaining this evolution have been widely described in literature, particularly in the case of hydrogen implanted silicon. Although fewer investigations have been done on others materials, similar mechanisms have been demonstrated for Ge (Ferain et al, 2010) and III-V compounds . Here, we review the main steps of this evolution inspired from silicon studies, which can be generally transposed to others materials (not in details).…”
Section: Layer Transfer Process: From Ion Implantation To Semiconductmentioning
confidence: 96%
“…Among various semiconductor materials, bulk Ge has the similar lattice constant as well as thermal expansion coefficient with GaAs, which enables the epitaxy of high crystalline quality GaAs on Ge surface [11][12][13]. In addition, many previous studies have indicated that the splitting and layer transfer of Ge can be realized by H implantation with the fluence less than half of that for the splitting of GaAs requires [14]. Therefore, other than the direct transfer of GaAs layer, a novel process consisting of the transfer of GaAs/Ge heterostructure via the splitting of Ge substrate has been proposed for the manufacturing of GaAs-on-insulator wafer, as illustrated in Fig.…”
Section: Introductionmentioning
confidence: 98%